Can Virtual Reality (VR) stimulate elementary school students' interest in learning? - Nugraini, Frisca Anghi; Abduh, Muhammad (Universitas Pakuan, 2025)
This research uses a qualitative approach with a case study design. This research aims to: 1) describe the use of Virtual Reality (VR) media as an effort to increase student interest at MIM PK Kertonantan, 2) describe the technical, non-technical and pedagogical obstacles for teachers in utilizing Virtual Reality (VR) learning media at MIM PK Kertonatan. The design of this research is a case study involving 1 teacher and several class VI students at MIM PK Kertonatan who participated in Virtual Reality (VR) based learning. Data was collected through in-depth interviews, direct observation and documentation, with the validity of the data guaranteed through triangulation of sources and techniques. Data analysis was carried out using a thematic approach, which allowed the identification of key themes related to the impact of Virtual Reality (VR). on interest in learning. The research results show that VR is able to create a more immersive and interactive experience. Students show increased enthusiasm and understanding of the material presented through Virtual Reality (VR) media. However, this research also reveals the challenges faced, such as limited technological infrastructure and teachers' lack of technical skills in operating Virtual Reality (VR) devices. This research concludes that although Virtual Reality (VR) has great potential in education, additional efforts are needed in teacher training and infrastructure development to support more effective implementation.